Transformation‐Invariant Laplacian Metadevices Robust to Environmental Variation - Huang, Yao; Zhang, Jingjing; Yang, Qianru; Meng, Lingsheng; Yang, Tianzhi; Qiu, Cheng‐Wei; Luo, Yu (Advanced materials (Weinheim), 2025)
As one of the typical applications of metamaterials, the invisibility cloak has raised vast research interests. After many years’ research efforts, the invisibility cloak has extended its applicability from optics and acoustics to electrostatics and thermal diffusion. One scientific challenge that has significantly restricted the practical application of the invisibility cloak is the strong background dependence, that is, all passive cloaking devices realized thus far are unable to resist variation in the background refractive index. To tackle such a challenge, the concept of transformation‐invariant metamaterials (TIMs) is applied to static‐field systems and shows that, for any physical fields governed by Laplace equation, judiciously designed TIMs can be used to realize invisibility cloaks robust to the environment variation. As an experimental proof, an ideal direct current (DC) cloak‐is implemented based on TIMs and near‐field measurement results demonstrate that such a cloak can successfully conceal a large‐scale object when the background conductivity varies from 22 to 859 kS m−1. Moreover, the background‐immune cloaking effect is observed under arbitrary electric sources. The approach proposed in this work can be also applied to static magnetics, thermal diffusion, and beyond, enabling robust isolation of the target from the external field in versatile application scenarios. Inspired by the recently proposed transformation‐invariant metamaterial, a DC cloak made of judiciously stacked copper/air multilayer is successfully constructed. It shows a robust cloaking performance even if the background conductivity varies from 22 to 859 kS m−1, which demonstrates significantly improved environment‐immune properties compared with those of conventional cloaks, for example traditional TO cloak and bi‐layer cloak.